miR-1258 Attenuates Tumorigenesis Through Targeting E2F1 to Inhibit PCNA and MMP2 Transcription in Glioblastoma - Qin, Hongkun; Gui, Yanping; Ma, Rong; Zhang, Heng; Guo, Yabing; Ye, Yuting; Li, Jia; Zhao, Li; Wang, Yajing (Frontiers in Oncology, 2021)
MicroRNAs are a group of endogenous small non-coding RNAs commonly dysregulated in tumorigenesis, including glioblastoma (GBM), the most malignant brain tumor with rapid proliferation, diffuse invasion, and therapeutic resistance. Accumulating evidence has manifested that miR-1258 exerts an inhibitory role in many human cancers. However, the expression pattern of miR-1258 and its potential function in GBM tumorigenesis remain unclear. In this study, we reported that miR-1258 expression decreased with the ascending pathological grade of glioma, which indicated an unfavorable prognosis of patients. Functional assays revealed an inhibitory effect of miR-1258 on malignant proliferation, therapeutic resistance, migration, and invasion of GBM in vitro. Moreover, xenograft models also suggested a repression effect of miR-1258 on gliomagenesis. Mechanistically, miR-1258 directly targeted E2F1 in 3’-untranslated regions and attenuated E2F1-mediated downstream gene PCNA and MMP2 transcriptions. Furthermore, restoration of E2F1 expression in GBM cells effectively rescued the tumor-suppressive effect of miR-1258. Our studies illustrated that miR-1258 functioned as a tumor suppressor in GBM by directly targeting E2F1, subsequently inhibiting PCNA and MMP2 transcriptions, which contributed to new potential targets for GBM therapy and other E2F1-driven cancers.